O papel da internet para as redes de organizações não-governamentais: o caso da Articulação de Mulheres Negras Brasileiras (AMNB) - Dias, Sonia Maria Barbosa (2009)
This study aims to investigate how the internet has become the instrument for coordination and mobilization of actions undertaken by networks of non-governmental organizations (NGOs), whereas the expansion of links between the participants of the network of NGOs is constituted in a capital increase of the network and its potential for articulation. This analysis is based on a survey conducted with members of the Coordination of Organizations of Black Brazilian Women (AMNB), composed of representatives of non-governmental organizations and social movements that work to combat racism and sexism. The AMNB was founded in 2000 by a group of black women members of NGOs from different regions of the country. The first part of the dissertation presents the assumptions and the main theoretical references which give rise to reflection about the impact of the use of resources made available by information and communication technologies (ICTs) to increase the field of relations of participants in networks of social movements, and with guiding the basis of analysis of social networks, from the approaches presented mainly by Granovetter (1973) and Wellman (2006, 2007), and resources accumulated in these relations, the social capital, from the theoretical references made by Bourdieu (1985), Coleman (1988), Lin (2001, 1999) and Portes (2000). It also gives a brief overview about the role of nongovernmental organizations (NGOs), key actors in social movements in Brazil. The second chapter gives a brief overview of studies and researches on the field of action that AMNB is engaged, inequalities of gender and race in Brazil, and the role played by AMNB in this scenario. In the end, are presented the data collected by research with the members of AMNB and analysis about the use of the Internet on the shares of AMNB and its members.